Systemic Immune-Inflammation Index Is Associated With Increased Urinary Albumin Excretion: A Population-Based Study - Qin, Zheng; Li, Hancong; Wang, Liya; Geng, Jiwen; Yang, Qinbo; Su, Baihai; Liao, Ruoxi (Frontiers in Immunology, 2022)
Background: Systemic immune-inflammation index (SII) is a novel inflammatory marker and inflammation has been reported to related with renal damage. We aimed to investigate the possible relationship between SII and albuminuria. Methods: The present cross-sectional study was conducted among adults with complete data about SII and urinary albumin-to-creatinine ratio (ACR) in 2005-2018 National Health and Nutrition Examination Survey (NHANES). SII was calculated as the platelet count ×neutrophil count/lymphocyte count. Albuminuria was defined as ACR > 30mg/g. Weighted multivariable regression analysis and subgroup analysis were conducted to explore the independent relationship between SII and albuminuria. Results: A total of 36463 individuals was included in our analysis. 9.56% participants categorized as albuminuria overall and increased with the higher SII tertiles (Tertile 1: 7.83%, Tertile 2: 8.49%, Tertile 3: 12.13%, P for trend<0.0001). Multivariable logistic regression showed that higher SII level was associated with increased likelihood of albuminuria independently (OR= 1.31, 95% CI: 1.17~1.48, P<0.0001) after fully adjustment. Subgroup analysis and interaction test showed that there was no significant dependence of gender, age, body mass index, hypertension, diabetes, non‐alcoholic fatty liver disease and eGFR on this positive association (all P for interaction >0.05). Conclusions: SII positively associated with increased urinary albumin excretion in US adults. Further large-scale prospective studies are still needed to analyze the role of SII in albuminuria.